2007
DOI: 10.1371/journal.pmed.0040023
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Graft-Versus-Host Disease in Humans by Donor Gene-Expression Profiling

Abstract: BackgroundGraft-versus-host disease (GVHD) results from recognition of host antigens by donor T cells following allogeneic hematopoietic cell transplantation (AHCT). Notably, histoincompatibility between donor and recipient is necessary but not sufficient to elicit GVHD. Therefore, we tested the hypothesis that some donors may be “stronger alloresponders” than others, and consequently more likely to elicit GVHD.Methods and FindingsTo this end, we measured the gene-expression profiles of CD4+ and CD8+ T cells f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
87
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 82 publications
(70 reference statements)
2
87
1
Order By: Relevance
“…Likewise, although not statistically significant, the probability of death due to hepatic veno-occlusive disease/thrombotic thrombocytopenic purpura was also increased, coinciding with previous findings of an association between veno-occlusive disease and TGF-β1 secretion. 34 In agreement with a study by Baron et al, who demonstrated that the donor gene-expression profile, in particular the TGF-β1 pathway, has a dominant influence on the development of GvHD, 35 we also found that the presence of the SNP at codon 10 in donors, as well as in patientdonor pairs, was associated with a higher incidence of acute GvHD and its clinically significant forms. This agrees with observations by Hattori et al, 25 who found that the wild-type donor genotype (TT) was protective for acute GvHD in an HLA-identical sibling donor pediatric cohort.…”
Section: Ii-iv (%) Iii-iv (%)supporting
confidence: 92%
“…Likewise, although not statistically significant, the probability of death due to hepatic veno-occlusive disease/thrombotic thrombocytopenic purpura was also increased, coinciding with previous findings of an association between veno-occlusive disease and TGF-β1 secretion. 34 In agreement with a study by Baron et al, who demonstrated that the donor gene-expression profile, in particular the TGF-β1 pathway, has a dominant influence on the development of GvHD, 35 we also found that the presence of the SNP at codon 10 in donors, as well as in patientdonor pairs, was associated with a higher incidence of acute GvHD and its clinically significant forms. This agrees with observations by Hattori et al, 25 who found that the wild-type donor genotype (TT) was protective for acute GvHD in an HLA-identical sibling donor pediatric cohort.…”
Section: Ii-iv (%) Iii-iv (%)supporting
confidence: 92%
“…We found that pre-AHCT gene-expression profiling segregates donors whose recipient suffered from GVHD or not. 19 The 'dangerous donor' trait (GVHD þ recipient) is under polygenic control and is shaped by the activity of genes that regulate TGF-b signaling and cell proliferation. The gene with the best GVHD predictive accuracy in our studies was SMAD3.…”
Section: Introductionmentioning
confidence: 99%
“…The gene with the best GVHD predictive accuracy in our studies was SMAD3. 19 No AHCT recipients suffered from GVHD when their donor cells expressed high levels of SMAD3 transcripts. 19 These data demonstrate that interindividual variations exist in the levels of SMAD3 transcripts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to identifying signatures or patterns of gene expression that represent a disease state, analyses can be constructed to identify representative pathway genes that might point to novel pathophysiology relevant to the underlying disease state. Peripheral blood gene expression signatures have now been reported in a variety of conditions including rheumatoid arthritis (Lequerré et al 2006;Shou et al 2006), systemic lupus erythematosis (Rus et al 2004), multiple sclerosis (Bomprezzi et al 2003;Singh et al 2007), asthma (Brutsche et al 2002), solid malignancies (Alizadeh et al 2000;Golub et al 1999;Valk et al 2004), solid organ transplantation (Baron et al 2007;Horwitz et al 2004), as well as environmental exposures (Lodovici et al 2007;Wu et al 2003;Dressman et al 2007) (see Table 1). Many of these conditions have an inflammatory component and thus affect immune cells in the vascular compartment.…”
Section: Introductionmentioning
confidence: 99%